Aptidão física de adolescentes com Síndrome de Down : um estudo de intervenção de 6 meses com acompanhamento longitudinal a 1 ano - Macêdo, Dafne Souto (2019)
Down syndrome is caused by a genetic disorder known as trisomy 21, which generates distinct health problems and consequently very low levels of physical fitness. Physical fitness that is considered an important health marker and a predictor of morbidity and mortality is a fundamental outcome to be analyzed because it seems to facilitate the continuous involvement in physical activities throughout life. The aim of this study was to compare the responses observed in physical fitness indicators (muscle strength, cardiorespiratory fitness, lean mass, fat mass, bone mineral content, flexibility, speed, agility and laterality) of adolescents with Down syndrome exposed to a 6-month multicomponent intervention program and to follow up these responses after 6 months and 1 year of intervention. The sample was composed of 14 adolescents with Down's Syndrome, living in the city of João Pessoa and participating in the "Escolinha + Movimento" project at the Federal University of Paraíba. Physical fitness was assessed by dual-emission Densitometry and physical tests constituting the battery Assessing Levels of Physical Activity (ALPHA) and Koordinations Test für Kinder (KTK). The mean and standard deviation were calculated. Friedman's variance analysis and non-parametric multivariate analysis of variance were used. The magnitude of the effect between the times was calculated using Cohen's d as reference. The analyzes were performed using the Software Statistical Package for Social Sciences - version 24.0 and the software R for nonparametric multivariate analysis of variance. There was a significant improvement in lean body mass (p = 0.003), strength (p = 0.015), velocity (p = 0.028) and agility (p = 0.003) 0.001). For flexibility, the results were marginally significant (p = 0.060). It is noteworthy that even after 1 year without intervention, the participants presented better values when compared with the baseline.